The artefacts of news - Palmer, Michael (Javnost (Ljubljana), 2003)
News is a contraction of two words: "new things." And news is the report of those "new things." These reports over time can themselves become artefacts. Historians, anthropologists, sociologists - along with journalists - study news. In different ways and via a range of media, dramatists, paleo-anthropologists and poets also pinpoint - sometimes en passant - the production, transmission and impact of news. Here we look at the seemingly unlikely "cross-fertilisation" of these remarks, and pick up points made by newsmen working at speed to capture "a defining moment," a story and its impact.
Keywords: mass media; množični mediji; obveščanje; informiranje; objektivnost